Manajemen Rantai Pasok Produk Beras di Penggilingan Padi Sumber Baru Kecamatan Sidoarjo, Kabupaten Sidoarjo: Rice Product Supply Chain Management in New Source Rice Milling in Sidoarjo District, Sidoarjo Regency - Kusuma, Inas Mufidati; Widayanti, Sri; Indah, Pawana Nur (Jurnal Ilmiah Manajemen Agribisnis, 2023)
Research Objectives 1) To analyze the institutions and supply chain members of the rice commodity in the New Sumber Padi Mill; 2) Analyze the supply chain management of rice commodities at the New Sumber Padi Mill; 3) Analyze supply chain trading margins and value chain analysis at the New Source Rice Mill. The analytical method used is descriptive qualitative analysis, quantitative descriptive analysis, and qualitative design. The institutions and supply chain members involved in the rice supply chain at the Sumber Baru Rice Mill are farmers, middlemen, rice millers, retailers, and consumers. The supply chain channel pattern has three supply chain channel patterns. The product flow occurs from farmers selling grain to rice in the hands of consumers. The financial flow of the two-channel patterns is equally profitable. Then the information flow occurs because each has a two-way flow of information between institutions and supply chain members. The trading system margin for each trading system channel is different. The highest added value is in the rice mill.